2015
DOI: 10.1016/j.neuron.2015.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Neuron Transplantation into Adult Visual Cortex Creates a New Critical Period that Rescues Impaired Vision

Abstract: The maturation of inhibitory circuits in the juvenile cortex triggers a critical period of plasticity in visual system development. Although several manipulations of inhibition can alter its timing, none have reactivated critical period plasticity in adulthood. We developed a transplantation method to reactivate critical period plasticity in the adult visual cortex. Transplanted embryonic inhibitory neurons from the medial ganglionic eminence reinstate ocular dominance plasticity in adult recipients. Transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(138 citation statements)
references
References 42 publications
5
129
2
Order By: Relevance
“…Most recently, however, it has been shown that somatostatin-containing, dendrite-innervating interneurons, which also arise from the MGE, are equally capable of inducing ocular dominance plasticity (Tang et al 2014). It is, therefore, remarkable that CGE explants, which give rise to diverse forms of mature interneurons, failed to induce plasticity in the present as well as in a concurrent (Davis et al 2015) study. In both studies, the transplanted CGE-derived cells preferentially settled in deep cortical layers, although intrinsic inhibitory interneurons from the CGE are mostly found in superficial layers (Miyoshi et al 2010).…”
Section: Transplantation Of Cge Fails To Induce Ocular Dominance Plasmentioning
confidence: 47%
See 2 more Smart Citations
“…Most recently, however, it has been shown that somatostatin-containing, dendrite-innervating interneurons, which also arise from the MGE, are equally capable of inducing ocular dominance plasticity (Tang et al 2014). It is, therefore, remarkable that CGE explants, which give rise to diverse forms of mature interneurons, failed to induce plasticity in the present as well as in a concurrent (Davis et al 2015) study. In both studies, the transplanted CGE-derived cells preferentially settled in deep cortical layers, although intrinsic inhibitory interneurons from the CGE are mostly found in superficial layers (Miyoshi et al 2010).…”
Section: Transplantation Of Cge Fails To Induce Ocular Dominance Plasmentioning
confidence: 47%
“…While it has been shown that they increase both inhibition of intrinsic excitatory cells (Alvarez-Dolado et al 2006;Southwell et al 2012) and ocular dominance plasticity (Davis et al 2015) independently of their density, a direct augmentation of inhibition by diazepam treatment does not induce plasticity in adult mice (Fagiolini and Hensch 2000). Moreover, the opposite intervention, namely reducing inhibition, can also reinstate ocular dominance plasticity in adult animals (Harauzov et al 2010).…”
Section: Transplantation Of Cge Fails To Induce Ocular Dominance Plasmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Neuron, Davis et al (2015) show that transplantation of embryonic inhibitory interneurons can reactivate critical period plasticity and reverse amblyopia in the visual cortex of adult mice.…”
mentioning
confidence: 98%
“…As exciting as these results were, however, a major limitation of this study was that transplantation was done in very young, pre-criticalperiod recipients ( Figures 1A and 1B), severely limiting its potential in clinical applications. In a study published in this issue of Neuron, Davis and colleagues in the Gandhi lab overcame this limitation by performing the vital, yet daunting, experiment of transplanting embryonic inhibitory neurons into adult mice (Davis et al, 2015).…”
mentioning
confidence: 99%